TERRITORIAL COMMUNITY AS A SUBJECT OF LOCAL GOVERNMENT IN UKRAINE - Липчук, О. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
In this article the essence of the concept of territorial community as a subject of local government. An important part of this study takes the analysis of the main problems and prospects of development of the local community in Ukraine. Practical advice I of the functioning of territorial communities at the present stage of development of local self-government in Ukraine.